Investigation of monoclonal antibody dimers in a final formulated drug by separation techniques coupled to native mass spectrometry - G. Rouby; N. T. Tran; Y. Leblanc; M. Taverna; N. Bihoreau (mAbs, 2020)
Therapeutic monoclonal antibodies (mAbs) are highly complex proteins that must be exhaustively characterized according to the regulatory authorities' recommendations. MAbs display micro-heterogeneity mainly due to their post-translational modifications, but also to their susceptibility to chemical and physical degradations. Among these degradations, aggregation is quite frequent, initiated by protein denaturation and then dimer formation. Here, we investigated the nature and structure of the high molecular weight species (HMW) present at less than 1% in an unstressed formulated roledumab biopharmaceutical, as a model of high purity mAb. HMW species were first purified through preparative size-exclusion chromatography (SEC) and then analyzed by a combination of chromatographic methods (ion-exchange chromatography (IEX), SEC) coupled to native mass spectrometry (MS), as well as sodium dodecyl sulfate–polyacrylamide gel electrophoresis and capillary gel electrophoresis under non-reducing conditions. Both covalently and non-covalently bound dimers were identified at a proportion of 50/50. In-depth characterization of the HMW fraction by SEC and IEX hyphenated to native MS revealed the presence of three mAb dimer forms having the same mass, but differing by their charge and size. They were attributed to different compact and elongated dimers. Finally, high-resolution middle-up approaches using different enzymes (IdeS and IgdE) were performed to determine the mAb domains implicated in the dimerization. Our results revealed that the roledumab dimers were associated mainly by a single Fab-to-Fab arm-bound association.